Long segment ureteral reconstruction using the prepuce: A case report - Xiaoyong Zeng; Zhenliang Qin; Xing Li; Jun Zhou; Shuai Lu; Weiwu Liu; Ying Zhan; Ruibao Chen (Urology Case Reports)
Long segment ureteral reconstruction has always posed a challenge for surgeons. We report the case of a 49 years male patient with a right ureteral obstruction between the ileal orthotopic bladder and the ureter. The patient underwent a 12cm ureteral reconstruction with the prepuce. One month after the surgery, anterograde angiography through the nephrostomy tube showed ureteral patency. After one year of postoperative follow-up, the patient's ureteral stricture did not recur. Using the prepuce as a free graft for ureteral reconstruction is one of the available options.